Engram-specific transcriptome profiling of contextual memory consolidation - Priyanka Rao-Ruiz (Nature Portfolio, 2019)
The molecular mechanisms underlying contextual fear memory consolidation by sparse dentate gyrus (DG) neuronal populations remain unclear. Here using unbiased RNA sequencing of DG engram neurons the authors identify persistent transcriptome modifications during memory consolidation, in which CREB-dependent transcription features prominently